Pediatric Coping During Venipuncture With Virtual Reality: Pilot Randomized Controlled Trial - Therese Canares; Carisa Parrish; Christine Santos; Alia Badawi; Alyssa Stewart; Keith Kleinman; Kevin Psoter; Joseph McGuire (JMIR Publications, 2021)
BackgroundVirtual reality (VR) has shown promise in reducing children's pain and anxiety during venipuncture, but studies on VR lack objective observations of pediatric coping. Notably, the process of capturing objective behavioral coping data can be labor- and personnel-intensive. ObjectiveThe primary aims of this pilot trial were to assess the feasibility of conducting a trial of VR in a pediatric emergency department and the feasibility of documenting observed coping behaviors during pediatric procedures. Secondarily, this study examined whether VR affects child and caregiver coping and distress during venipuncture in the pediatric emergency department. MethodsThis stratified, randomized, controlled pilot trial compared coping and distress between child life-supported VR engagement and child life specialist support without VR during painful procedures in children aged 7-22 years in the pediatric emergency department. An external control (reference group) received no standardized support. Primary feasibility outcomes included rates of recruitment, rates of withdrawal from VR, and rates of completed Child Adult Medical Procedure Interaction Scale-Short Form (CAMPIS-SF) observations. Secondary clinical outcomes were applied to venipuncture procedures and included CAMPIS-SF coping and distress (range 0-1.0), pain and anxiety on a visual analog scale (range 0-10), and cybersickness symptoms. ResultsOverall recruitment was 93% (66/71), VR withdrawal rate was 27% (4/15), and of the completed procedures, 100% (63/63) CAMPIS-SF observations were completed. A total of 55 patients undergoing venipuncture in the pediatric emergency department were included in the analyses of clinical outcomes: 15 patients (15 caregivers) randomized to VR, 20 patients (15 caregivers) randomized to child life specialist support, and 20 patients (17 caregivers) in the reference group. Patient coping differed across groups with higher coping in the VR group and child life specialist group than in the reference group (P=.046). There were no significant differences in the distress and pain ratings for patients and caregivers between the groups. Caregivers rated the lowest perceived anxiety in the child life specialist group (P=.03). There was no apparent change in cybersickness symptoms before and after VR use (P=.37). ConclusionsReal-time documentation of observed behaviors in patients and caregivers was feasible during medical procedures in which VR was utilized, particularly with the availability of research staff. VR and child life specialists improved coping in children during venipuncture procedures. Given the high participation rate, future studies to evaluate the efficacy of VR are recommended to determine whether an off-the-shelf VR headset can be a low-cost and low-risk tool to improve children's coping during venipuncture or other related procedures. Trial RegistrationClinicalTrials.gov NCT03686176; https://clinicaltrials.gov/ct2/show/NCT03686176